"Proactive" in many ways: Developmental evidence for a dynamic pluralistic approach to prediction. Issue 11 (1st November 2016) - Mani, Nivedita; Daum, Moritz M; Huettig, Falk
Abstract : The anticipation of the forthcoming behaviour of social interaction partners is a useful ability supporting interaction and communication between social partners. Associations and prediction based on the production system (in line with views that listeners use the production system covertly to anticipate what the other person might be likely to say) are two potential factors, which have been proposed to be involved in anticipatory language processing. We examined the influence of both factors on the degree to which listeners predict upcoming linguistic input. Are listeners more likely to predict book as an appropriate continuation of the sentence "The boy reads a", based on the strength of the association between the words read and book (strong association) and read and letter (weak association)? Do more proficient producers predict more? What is the interplay of these two influences on prediction? The results suggest that associations influence language-mediated anticipatory eye gaze in two-year-olds and adults only when two thematically appropriate target objects compete for overt attention but not when these objects are presented separately. Furthermore, children's prediction abilities are strongly related to their language production skills when appropriate target objects are presented separately but not when presented together. Both influences on prediction in language processing thus appear to be context dependent. We conclude that multiple factors simultaneously influence listeners' anticipation of upcoming linguistic input and that only such a dynamic approach to prediction can capture listeners' prowess at predictive language processing.